Clinical Features of Graves' Ophthalmopathy and Impact of Enalapril on the Course of Mild Graves’ Ophthalmopathy: A Pilot Study - Ataabadi, Ghazal; Dabbaghmanesh, Mohammad H.; Owji, Naser; Bakhshayeshkaram, Marzieh; Montazeri-Najafabady, Nima (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Inflammation, oxidative stress, and adipogenesis are associated with Graves’ ophthalmopathy (GO) progression. Objective: We conducted a pilot study to investigate the effect of Enalapril on patients with mild ophthalmopathy. Method: Based on the comprehensive eye examination, 12 patients with mild ophthalmopathy were selected from referred Graves’ patients and treated with Enalapril (5 mg daily) for 6 months. Clinical and ophthalmological examination [IOP (Intraocular Pressure), vision, Margin reflex distance and exophthalmia measurement, CAS (clinical activity score) and VISA [V (vision); I (inflammation/ congestion); S (strabismus/motility restriction); and A (appearance/exposure] score assessment) was performed at the beginning, 3 months and 6 months of the study period. Quality of life was also evaluated using a standard questionnaire. Results: Mean exophthalmia at the first visit was 18.75 ± 2.39, 3 months later 18.53 ± 2.39 and 6 months later was 17.92 ± 2.31, respectively. Mean CAS was 0.71 ± 0.82 (first visit), 0.57 ± 0.54 (3 months) and 0.14 ± 0.36 (6 months), respectively. Mean Margin reflex distance was 9.09 ± 4.36 (first visit) and 9.60 ± 4.40 (6 months), respectively. There were significant differences in the case of exophthalmia (P=0.002), CAS (P=0.006), and Margin reflex distance (P=0.029) between the first visit and 6 months after treatment. The difference between the score of quality of life in patients with GO after 6 months of follow up was statistically significant (P = 0.006). Conclusion: Our results showed that Enalapril treatment could ameliorate the clinical course of GO according to the ophthalmologic examinations and subjective parameters of disease progression. However, further studies should be performed to determine the efficacy of Enalapril in Graves’ ophthalmopathy treatment.
Keywords: angiotensinconverting enzyme inhibitors